Floral biology, pollination ecology and seed production of the ornamental plant Salvia splendens Sello - Sánchez, Luis Alejandro (2002)
In this paper, the floral biology and pollination ecology of Salvia splendens are described. All flower characteristics (red corolla, large tubular flowers with abundant but dilute nectar) indicate that S. splendens is adapted to hummingbird pollination. Honeybees, however, were also found to be good pollinators of this plant. Apis mellifera was equally effective in pollinating S. splendens as hand pollination and open pollination, resulting in a 300% increase in seed set compared with bagged control plants. The much smaller stingless bee Tetragonisca angustula was not an effective pollinator of these flowers since during visitation its body failed to touch the stigma. Although pollination seemed not to be the only limiting factor in seed production, external pollinators enhance seed production in S. splendens, and Apis mellifera is an effective, commercially available pollination agent of this economically important ornamental plant.